2022
DOI: 10.1002/ejic.202200382
|View full text |Cite
|
Sign up to set email alerts
|

Three Proton‐Conductors Based on Keggin‐Type Polyoxometalates Well‐Arranged in the Networks of Dinuclear‐Cu(II)‐Mixed‐Organic‐Ligand Clusters

Abstract: Three proton‐conductors, [Cu(5‐H2L)(IN)(H2O)]2H2[SiW12O40] ⋅ 2CH3CN ⋅ 2.5H2O (1), [Cu(4‐HL)(HIN)(H2O)]2H2[SiW12O40] ⋅ 7H2O (2) and [Cu(4‐HL)(HIN)(CH3CN)]2[HIN]2H4[PMo12O40]2 ⋅ 2CH3CN ⋅ 12H2O (3) (where 5‐H2L/4‐H2L is 5,5’/4,4’‐bis(hydroxymethyl)‐2,2’‐bipyridine and HIN is isonicotinic acid), were synthesized at room temperature. Interestingly, three dinuclear‐Cu(II)‐mixed‐organic‐ligand clusters, [Cu(5‐H2L)(IN)(H2O)]22+ cluster for 1, [Cu(4‐HL)(HIN)(H2O)]22+ for 2 and [Cu(4‐HL)(HIN)(CH3CN)]22+ for 3, are in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…As shown in Figure a,b, conductivity depends closely on the specific RH at 35 °C. The value increased from 4.8 × 10 –4 (55% RH) to 1.2 × 10 –3 S cm –1 (70% RH), which is superior to the conductivity of most reported proton-conductive POMs under similar conditions. With increasing temperature, the conductivity increased rapidly and achieved 1.2 × 10 –2 S cm –1 as the maximum at 85 °C (Figure c,d), which is among the highest proton conductivities yet found in POM-based materials under similar operating conditions (Table S4), holding great prospects as solid electrolytes in proton-exchange membrane (PEM) fuel cells. ,,, The research data has shown that the proton-conductive performance of DMA-KNaLi-As 10 is heavily affected by a combined impact of temperature and RH. Clearly, the proton transport in DMA-KNaLi-As 10 might be markedly enhanced under hot and humid environments.…”
Section: Resultsmentioning
confidence: 85%
“…As shown in Figure a,b, conductivity depends closely on the specific RH at 35 °C. The value increased from 4.8 × 10 –4 (55% RH) to 1.2 × 10 –3 S cm –1 (70% RH), which is superior to the conductivity of most reported proton-conductive POMs under similar conditions. With increasing temperature, the conductivity increased rapidly and achieved 1.2 × 10 –2 S cm –1 as the maximum at 85 °C (Figure c,d), which is among the highest proton conductivities yet found in POM-based materials under similar operating conditions (Table S4), holding great prospects as solid electrolytes in proton-exchange membrane (PEM) fuel cells. ,,, The research data has shown that the proton-conductive performance of DMA-KNaLi-As 10 is heavily affected by a combined impact of temperature and RH. Clearly, the proton transport in DMA-KNaLi-As 10 might be markedly enhanced under hot and humid environments.…”
Section: Resultsmentioning
confidence: 85%